2014
DOI: 10.5840/beq20143206
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perceived Corporate Social Responsibility on Employee Attitudes

Abstract: ABSTRACT:We explore the impact on employee attitudes of their perceptions of how others outside the organization are treated (i.e., corporate social responsibility) above and beyond the impact of how employees are directly treated by the organization. Results of a study of 827 employees in eighteen organizations show that employee perceptions of corporate social responsibility (CSR) are positively related to (a) organizational commitment with the relationship being partially mediated by work meaningfulness and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
516
2
31

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 492 publications
(568 citation statements)
references
References 117 publications
19
516
2
31
Order By: Relevance
“…Zhu et al [15] demonstrated the significant relationship between employee perceptions of organizational effort on CSR and satisfaction. Similarly, Glavas and Kelly [48] found that CSR perceptions are positively related to job satisfaction. In addition, Roecka et al [45] found internal and external CSR perceptions are positively related to job satisfaction.…”
Section: Moderating Role Of Person-csr Fitmentioning
confidence: 99%
“…Zhu et al [15] demonstrated the significant relationship between employee perceptions of organizational effort on CSR and satisfaction. Similarly, Glavas and Kelly [48] found that CSR perceptions are positively related to job satisfaction. In addition, Roecka et al [45] found internal and external CSR perceptions are positively related to job satisfaction.…”
Section: Moderating Role Of Person-csr Fitmentioning
confidence: 99%
“…An experiment by Balakrishnan, Sprinkle, and Williamson (2011) discovered that employees demonstrated increased motivation even though they were not personally benefitting from the CSR actions. This was also discovered by (Glavas & Kelley, 2014). A study by Raub and Blunschi (2013) also demonstrated that CSR helped employees attain better job satisfaction.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Furthermore, organizations such as banks and other corporate entities are particularly interested in the aspect of shareholder value and competitive advantage (Lo & Sheu, 2010). Moreover, more and more studies have alluded to the fact that there might be more to the concept, and that employees perception of CS in the organization could in fact influence their extra role behaviour (Farooq et al, 2016), job satisfaction (Dhonesh, 2014), well-being and feeling of meaningfulness (Glavas, 2014) or their engagement (Glavas & Piderit, 2009) among other attitudinal and behavioural outcomes. Arguably, since studies on the specific impact of CS of employee engagement are unclear (Glavas & Piderit, 2009), and further challenging due to its multi-discipline application (Bansal & Song, 2017).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%